Topical Anti‐Inflammatory Treatments for Eczema: A Cochrane Systematic Review and Network Meta‐Analysis - Lax, Stephanie J.; Van Vogt, Eleanor; Candy, Bridget; Steele, Lloyd; Reynolds, Clare; Stuart, Beth; Parker, Roses; Axon, Emma; Roberts, Amanda; Doyle, Megan; Chu, Derek K.; Futamura, Masaki; et al. (Clinical and experimental allergy, 2024)
ABSTRACT Objective Eczema is the most burdensome skin condition worldwide and topical anti‐inflammatory treatments are commonly used to control symptoms. The relative effectiveness and safety of different topical anti‐inflammatory treatments is uncertain. Design Network meta‐analysis performed within a Cochrane systematic review to compare and statistically rank efficacy and safety of topical anti‐inflammatory eczema treatments. Data Sources Cochrane Skin Specialised Register, CENTRAL, MEDLINE, Embase and trial registries to June 2023. Eligibility Criteria for Selected Trials Included trials were within‐participant or between‐participant randomised controlled trials. Participants had eczema that was not clinically infected and was not contact dermatitis, seborrheic eczema or hand eczema. Interventions were topical anti‐inflammatory treatments but not complementary treatments, antibiotics alone, wet wraps, phototherapy or systemic treatments. Comparators were no treatment/vehicle or another topical anti‐inflammatory. Results We identified 291 trials (45,846 participants), mainly in high‐income countries. Most were industry‐funded with median 3 weeks treatment duration. Risk of bias assessed using the Cochrane Risk of Bias 2.0 tool was high in 89% of trials, mainly due to risk of selective reporting. Network meta‐analysis of binary outcomes ranked potent and/or very potent topical steroids, tacrolimus 0.1% and ruxolitinib 1.5% among the most effective treatments for improving patient‐reported symptoms (40 trials, all low confidence) and clinician‐reported signs (32 trials, all moderate confidence). For investigator global assessment, the Janus kinas inhibitors ruxolitinib 1.5%, delgocitinib 0.5% or 0.25%, very potent/potent topical steroids and tacrolimus 0.1% were ranked as most effective (140 trials, all moderate confidence). Continuous outcome data were mixed. Local application site reactions were most common with tacrolimus 0.1% (moderate confidence) and crisaborole 2% (high confidence) and least common with topical steroids (moderate confidence). Skin thinning was not increased with short‐term use of any topical steroid potency (low confidence) but skin thinning was reported in 6/2044 (0.3%) participants treated with longer‐term (6–60 months) topical steroids. Conclusion Potent topical steroids, Janus kinase inhibitors and tacrolimus 0.1% were consistently ranked as among the most effective topical anti‐inflammatory treatments for eczema. Trials of topical anti‐inflammatory eczema treatments are mostly industry‐funded, evaluate short‐term outcomes and carry a high risk of bias due to selective reporting. Data from almost 300 trials suggest that potent steroids, Janus kinase inhibitors and tacrolimus 0.1% are among the most effective topical treatments. Local reactions were most common with tacrolimus 0.1% and crisaborole and least common with steroids.